Wireless sensor network - Zheng, Shaohua. (2010)
The existing problem of indoor wireless network is the supply of energy. This project aims to find solutions to the energy problem by looking into harvesting of ambient energy namely piezoelectric harvesting and solar energy harvesting. To achieve that, tasks of finding information on wireless network and energy harvesting were undertaken in order to conduct tests and experiments for analysis. This report begins by introducing the various technologies and history behind the operations of the wireless sensor network and the energy harvesting techniques of piezo and solar. Then the structure of both systems will be explained using diagrams. Calculations and observations are then compared and analyzed in terms of effectiveness and power to show how well the power harvesting unit supports the wireless system by transmitting sensor data. At the end of the project we conclude the feasibility of ambient power harvesting applications and what are the limitations at the current technological level and also discuss what the future outlook of such applications is.